Evaluation of the therapeutic response of hepatitis C in coinfected patients (HIV/HCV): a study of cases from a hospital for chronic liver diseases in the Eastern Brazilian Amazon - AMARAL, Ivanete do Socorro Abraçado (2014)
INTRODUCTION: The aim of this study was to evaluate the therapeutic response of hepatitis C in patients coinfected with human immunodeficiency virus (HIV-1). METHODS: A retrospective study of 20 patients coinfected with HIV-1/HCV who were treated in the outpatient liver clinic at the Sacred House of Mercy Foundation Hospital of Pará (Fundação Santa Casa de Misericórdia do Pará - FSCMPA) from April 2004 to June 2009. Patients were treated with 180µg PEG interferon-α2a in combination with ribavirin (1,000 to 1,250mg/day) for 48 weeks. The end point was the sustained virological response (SVR) rate (HCV RNA negative 24 weeks after completing treatment). RESULTS: The mean age of the patients was 40±9.5 years, of which 89% (n=17) were male, and the HCV genotypes were genotype 1 (55%, n=11/20), genotype 2 (10%, n=2/20) and genotype 3 (35%, n=7/20). The mean CD4+ lymphocyte count was 507.8, and the liver fibrosis stages were (METAVIR) F1 (25%), F2 (55%), F3 (10%) and F4 (10%). The early virological response (EVR) was 60%, the end-of-treatment virological response (EOTVR) was 45% and the SVR was 45%. CONCLUSIONS: The median HCV viral load was high, and in 85% of cases in which highly active antiretroviral therapy (HAART) was used, none of the patients with F3-F4 fibrosis responded to treatment. Of the twenty patients treated, 45% achieved SVR and 45% achieved EOTVR. Studies that include cases from a wider region are needed to better evaluate these findings.